Prevalence of pancreaticobiliary reflux in symptomatic cholelithiasis and its significance - Bohara, TP; Parajuli, A; Bajracharya, GR; Joshi, MR (Journal of College of Medical Sciences-Nepal, 2014)
Aims: Pancreaticobiliary reflux (PBR) is reflux of pancreatic enzymes into the biliary tree which occurs as a result of an anamoly of pancreaticobiliary junction (PBJ) or functionally impaired sphincter. PBR is associated with changes in biliary epithelium and is known to cause benign and malignant biliary pathology. Various authors have reported prevalence of PBR in patients with normal PBJ ranging from 20 % to 83.5 %. With aim to detect the prevalence of PBR in patients with symptomatic cholelithiasis in Nepalese population we conducted this study. Materials and methods: Thirty patients undergoing elective laparoscopic cholecystectomy (LC) for symptomatic cholelithiasis were included in the study. History, physical findings and relevant investigations including liver function test, serum amylase and abdominal ultrasound were recorded. Bile sample for amylase was taken from gall bladder during LC percuatneously before manipulation of calot’s triangle and common bile duct. Bile amylase level above serum amylase level was considered positive for PBR. Results: Mean age of the patient was 37.27 (± 14.41) years. Out of 30, 6 (20 %) patients were male and 24 (80 %) were female. Mean BMI was 21.58 (± 3.2). PBR reflux was present in 66.7 % of patients out of which 2 were male and 18 were female that was not statistically significant (p = 1.41) when compared with patients without PBR. Conclusion: PBR occurs in patient with cholelithiasis and has role in pathogenesis of gallstones disease and gall bladder carcinoma. Long term surveillance would be required to ascertain the significance of detection of PBR after LC. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-1, 1-6 DOI: http://dx.doi.org/10.3126/jcmsn.v9i1.9666